Aspects of ancient institutions and geography : studies in honor of Richard J.A. Talbert - Brice, Lee L.; Slootjes, Daniëlle.; Talbert, Richard J. A., 1947- (Impact of Empire, 2015)
In Aspects of Ancient Institutions and Geography colleagues and students honor Richard J.A. Talbert for his numerous contributions and influence on the fields of ancient history, political and social science, as well as cartography and geography. This collection of original and useful examinations is focused around the core theme of Talbert's work - how ancient individuals and groups organized their world, through their institutions and geography. The first half of the book considers institutional history in chapters on such diverse topics as the Roman Senate, Roman provincial politics and administration, healing springs, gladiators, and soldiers. Chapters on the geography of Thucydides and Alexander III, imperial geography, tracking letters and using sundials round out the second half of the book.